2015
DOI: 10.1088/0957-4484/26/40/405602
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of graphene oxide/alginate composite hydrogels for enhanced adsorption of hydrophobic compounds

Abstract: Carbon-based materials, consisting of graphene oxide (GO) or reduced GO (rGO), possess unique abilities to interact with various molecules. In particular, rGO materials hold great promise for adsorption and delivery applications of hydrophobic molecules. However, conventional production and/or usage of rGO in aqueous solution often causes severe aggregation due to its low water solubility and thus difficulties in handling and applications. In our study, to prevent the severe aggregation of GO during reduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…WPI and rGO contain hydrophilic groups which contribute to the enhanced water sorption ability of the hydrogels. Some researchers reported similar findings in which the addition of rGO to hydrogel enhanced the swelling capacity of hydrogels [31,32]. However, it is important to mention that the hydrogel GW4 containing only rGO exhibited low swelling ability at pH 7.4 and at a temperature of 24 °C, indicating suppressed swelling ability and suggesting good mechanical property that is not easily destroyed by swelling forces.…”
Section: Discussionmentioning
confidence: 68%
“…WPI and rGO contain hydrophilic groups which contribute to the enhanced water sorption ability of the hydrogels. Some researchers reported similar findings in which the addition of rGO to hydrogel enhanced the swelling capacity of hydrogels [31,32]. However, it is important to mention that the hydrogel GW4 containing only rGO exhibited low swelling ability at pH 7.4 and at a temperature of 24 °C, indicating suppressed swelling ability and suggesting good mechanical property that is not easily destroyed by swelling forces.…”
Section: Discussionmentioning
confidence: 68%
“…Moreover, Raman spectra showed that the reduction degree of GO increased with increasing Ni content. This was one of the key factors to enhance the adsorption capacity in the removal of organic contaminants [58,59]. …”
Section: Adsorption Kinetics and Photodegradation Of Rhodamine B(rhb)mentioning
confidence: 99%
“…Several chemical and physical routes are available for partially restoring the honeycomb structure and removing the functional groups [16]. The resulted reduced graphene oxide (RGO) can have great potential in hydrogel nanocomposites as its properties are close to that of the graphene, but its hydrophobicity is decreased [17]. Nowadays GO containing systems are in the focus of attention [18][19][20][21] and few attempts have been already made to prepare various RGO containing composite materials [22][23][24][25][26] as well.…”
Section: Introductionmentioning
confidence: 99%
“…reduction agent added to the initial precursor mixture) may be used [28,29]. An effective way to make RGO containing gel composites is to reduce the already incorporated GO inside the gel matrix [30,31], however the circumstances of the reduction (e.g. reducing agent, temperature) should be chosen with great care in order not to affect the physical/chemical properties of the gel.…”
Section: Introductionmentioning
confidence: 99%